Web information retrieval and monitoring using adaptive agent / Chong Yuen Beng - Chong, Yuen Beng (2001)

(untitled)
Internet is the information house. There are million of pages posted in the Internet, and still growing in exponential. Locate a web page, without a search engines, is like a blind explorer. There are many search engines in the existence world, but more new search engines is under construction. Each search engine has its advantage and disadvantage, depend on the need of the searchers. The projects aims to develop an agent, with some advanced features, to allow the searchers obtain the information from the Internet easily. The advanced features included, table of contents preview, chart of relevant, session review and resuming, etc. In addition, the system has the ability to learn, allow the system to grown without the help from the human. As the information in the Internet is expanding, editing the system's knowledge is not an easy task.